2004
DOI: 10.1111/j.1365-2044.2004.03803.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an epidural analgesic admixture containing epinephrine, fentanyl and bupivacaine

Abstract: SummaryThe addition of epinephrine to solutions containing fentanyl and bupivacaine for epidural infusion has been shown to improve the quality of analgesia. However, this admixture is not available commercially in the United Kingdom. Moreover, stability data applicable to UK practice for this admixture are limited. This study investigated the stability of fentanyl 2 lg.mlplus bupivacaine 1 mg.ml )1 in PVC bags with and without epinephrine 2 lg.ml )1 over a period of 184 days both at room temperature and at 4°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…As the results show that neither of the solution concentrations falls below the 95% starting concentration limit, we considered both solutions stable. This corresponds with previous studies 10 12 14…”
Section: Resultssupporting
confidence: 93%
“…As the results show that neither of the solution concentrations falls below the 95% starting concentration limit, we considered both solutions stable. This corresponds with previous studies 10 12 14…”
Section: Resultssupporting
confidence: 93%
“…In some studies, no major change in the epinephrine concentration has been found after several months of storage at room temperature . Allen et al stored a bupivacaine–fentanyl–epinephrine admixture for one month and detected a 8% decline in the epinephrine concentration, Priston et al observed about a 7% and Kjonniksen et al approximately a 3·5% reduction after 6 months at room temperature. In contrast, Dawson et al claimed that at 35 °C nearly 40% of epinephrine degraded progressively over 56 days and the rate was not affected by the presence of room light.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC methods were based on previously published methods, which were modified and their ability to monitor stability was evaluated during validation studies. Briefly, an Agilent Technologies 1100 HPLC system (Agilent Technologies Inc., Waldbronn, Karlsruhe, Germany) employing a binary pump, micro‐vacuum degasser, autosampler, thermostatted column compartment, diode array detector, fluorescent detector and Agilent Technologies Chemstation ® for LC 3D Software (Rev.…”
Section: Methodsmentioning
confidence: 99%
“…In one such study, a solution containing the same three active ingredients in the same concentrations was made using an adrenaline solution for injection that contained 0.95 μg/ml sulphite (epinephrine injection BP, Phoenix Pharma, Gloucester, UK). The stability of that solution was documented for 184 days at both 4°C and 22°C . In another study, a solution containing levobupivacaine (570 μg/ml), fentanyl (3.7 μg/ml), and adrenaline (1.9 μg/ml) was shown to be stable for 60 days at 6°C and 40 days at 22°C .…”
Section: Discussionmentioning
confidence: 98%